Management Plan of Irrigation for Yield Improvement Agriculture, Trucuk District, Bojonegoro Regency - Arobi, M. Sultoni; Waluyo, Budi Sugiarto; Usman, Fadly (Civil and Environmental Science Journal (CIVENSE), 2025)
Trucuk Subdistrict in Bojonegoro Regency, Indonesia, possesses considerable agricultural potential, yet its productivity remains limited due to inefficient irrigation systems. Damaged irrigation networks have led to inadequate water distribution, which indicates the importance of effective operation and maintenance strategies. This study aims to assess the existing condition of the Trucuk Irrigation Area (DI Trucuk) and determine management priorities to ensure a reliable water supply for agricultural land. A quantitative approach was employed using evaluative and management priority analysis, focusing on key irrigation components such as main buildings, control buildings, and secondary and tertiary canals. The results reveal that several irrigation channels, particularly GYN-5 and SRK-12, are severely damaged, with respective damage scores of 0.46 and 0.42. Although some channels, including GYN-5, SRK-12, and GYN-2, recorded the highest functional values, they were still poorly functioning. Based on a priority analysis, rehabilitation of GYN-5, GYN-2, SRK-12, and SRK-11 is recommended. Additionally, routine and regular maintenance of other irrigation channels and buildings is needed to ensure efficient and effective water distribution to agricultural areas. The proposed management plan offers a practical solution to improve irrigation performance and supports sustainable agrarian productivity in Trucuk Subdistrict.